Occupational Sex Segregation and Working Time: Regional Evidence from Germany - Humpert, Stephan (Panoeconomicus, 2014)
This paper provides descriptive evidence for declining occupational sex segregation on the German labor market, especially concerning the regional differences between the former East and West Germany. I use segregation measures and long-run social security data for the decade of 1992 to 2004. While segregation has declined over time, it remains higher for the eastern part of Germany. Although this finding is observable for full-time and part-time work, segregation is always lower in part-time employment. Key words: Gender, Segregation, Germany. JEL: J16, J23.